2022
DOI: 10.32604/jrm.2022.019602
|View full text |Cite
|
Sign up to set email alerts
|

Curing Kinetics of Tannin and Lignin Biobased Adhesives Determined by DSC and ABES

Abstract: The curing process of two biobased adhesives: pine tanninhexamine (TH) and organosolv lignin non-isocyanate polyurethane (NIPU), suitable for interior nonstructural use, were compared with commercial urea-formaldehyde (UF) adhesive. Changes in chemical structure before and after the curing process were observed with Fouriertransform infrared spectroscopy (FTIR). The process of adhesive curing was monitored with differential scanning calorimetry (DSC) and the automated bonding evaluation system (ABES). Both DSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
(28 reference statements)
0
10
0
1
Order By: Relevance
“…The same as for the peak at 1595 cm -1 in LW true for the peak at 1450 cm -1 , which signaled the asymmetric CH 3 bending of the methoxyl groups (O-CH 3 ) in the lignin structure [31]. In contrast, a shoulder peak at 1550 in LW+HMDA indicated the presence of secondary amides (N-H bonds) [34]. A bending vibration at about 1250 cm -1 was characteristic of the C-O-C groups of the ether linkages originating from the lignin in LW.…”
Section: Ftir Spectramentioning
confidence: 59%
“…The same as for the peak at 1595 cm -1 in LW true for the peak at 1450 cm -1 , which signaled the asymmetric CH 3 bending of the methoxyl groups (O-CH 3 ) in the lignin structure [31]. In contrast, a shoulder peak at 1550 in LW+HMDA indicated the presence of secondary amides (N-H bonds) [34]. A bending vibration at about 1250 cm -1 was characteristic of the C-O-C groups of the ether linkages originating from the lignin in LW.…”
Section: Ftir Spectramentioning
confidence: 59%
“…Additionally, when comparing the FTIR spectra of the HKL and NIPU, the width of the broad peak of the -OH group of 3100-3500 cm −1 in the HKL is considerably narrower in the NIPU. It is due to the evaporation of water during the crosslinking process and the condensation reaction between hydroxymethyl groups or hydroxymethyl groups and NH 2 groups [69]. The peak at 1033 cm −1 is also associated with the Si-O-C and Si-O-Si bonds in the silane crosslinker (GPTMS) [66].…”
Section: Ftir Analysis Of Nipu Adhesivesmentioning
confidence: 99%
“…The lignin molecule can be used in a variety of value-added applications due to differences in molecular weight, elemental composition, and the types and proportions of functional groups. Saražin et al investigated the potency of organosolv lignin-based non-isocyanate polyurethane for wood adhesive and the result demonstrated satisfactory mechanical properties [66] and its curing kinetics for interior furniture showed that it was more suitable than urea-formaldehyde (UF) adhesive [67]. Sulfur-free lignin is produced by isolating lignin from the formacell process.…”
Section: Prospective Application Of Formacell Lignin As Advanced Bioc...mentioning
confidence: 99%